Decreased gray matter volume in inferior frontal gyrus is related to stop-signal task performance in alcohol-dependent patients. Issue 2 (30th August 2015) - Wiers, Corinde E.; Gawron, Christiane K.; Gröpper, Sonja; Spengler, Stephanie; Stuke, Heiner; Lindenmeyer, Johannes; Walter, Henrik; Bermpohl, Felix
Abstract: Impairment in inhibitory control has been proposed to contribute to habitual alcohol use, abuse and eventually dependence. Moreover, alcohol-dependent (AD) patients have shown a loss of gray matter volume (GMV) in the brain, specifically in prefrontal regions associated with executive functions, including response inhibition. To date, no study has evaluated whether this prefrontal GMV reduction is related to response inhibition in alcohol dependence. To address this issue, we acquired high-resolution T1-weighted magnetic resonance mages from recently detoxified AD patients ( n =22) and healthy controls (HC; n =21). Differences in local GMV between groups were assessed by means of voxel-based morphometry (VBM). Moreover, within the AD group, mean local GMV reductions were extracted and correlated with behavioral performance on the stop-signal task. We found a significantly decrease in GMV in the left inferior frontal gyrus (IFG) in AD patients compared with HC subjects. Further, mean local GMV in this area correlated positively with reaction times on go trials during the stop-signal task in AD patients. Our findings suggest that GMV losses in the IFG in AD patients are related to faster go responses on the stop-signal task. Highlights: Reduced gray matter volume (GMV) in left interior frontal gyrus (IFG) in alcoholics. IFG volumes correlate with RTs on stop-signal go trials but not SSRTs in alcoholics. GMV losses in IFG may be related to faster stop-signal task performance in alcoholism.